The politics of the pantry : stories, food, and social change - Mikulak, Michael (McGill-Queen's University Press, 2013)
""What's for dinner?" has always been a complicated question. The locavore movement has politicized food and challenged us to rethink the answer in new and radical ways. Questions about where our food comes from have moved beyond 100-mile-dieters into the mainstream. Celebrity chefs Jamie Oliver and Alice Waters, alternative food gurus such as Michael Pollan, and numerous other commentators have talked about the importance of understanding the sources and transformation of food on a human scale. In The Politics of the Pantry, Michael Mikulak interrogates these narratives--what he calls "storied food"--In food culture. He examines food's past and present relationship to environmentalism as well as competing narratives of food, pleasure, sustainability, and value that have emerged from the growing sustainable food movement in order to understand the potential and the limits of food politics. He also considers whether or not sustainable food practices can address questions about health, environmental sustainability, local economic development, and ethical globalization. An innovative synthesis of academic analysis, poetic celebration, and autobiography, The Politics of the Pantry provides anyone interested in the future of food and the emergence of a green economy with a better understanding of how what we eat is transforming the world."--Jacket.